Uruguay. Ein lateinamerikanisches Modell? - Koch, Ernesto (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
A history of social struggles in Uruguay is given, from the fights against the Spaniards in early 19th century until the present time. These fights were always influenced by imperialist appropriation of the country. After the Spain has withdrawn it was at first the English Imperialism, later the US-Imperialism which forced Uruguay’s economy to serve its needs. A comprise between rival fractions of Uruguay’s ruling class brought the country a long lasting period of stability and also some social reforms. Economic crisis, increasing social protest and a brutal military regime ended this period in the early seventies. A broad coalition of the Left Frente Amplio could not only survive the military regime, it grew continuously under democratic conditions. Since 1989 Frente Amplio rules in Montevideo, capital and biggest department of the country, and in 2004, its candidate won the presidential elections, starting a new economic policy as well as a new foreign policy.